EGO DISTONIK PADA TOKOH UTAMA NOVEL MAROON (LUKA SANG PENULIS) KARYA ASRINI MAHDIA - Zona Rida Rahayu (Program Studi Pendidikan Bahasa Indonesia, , Fakultas Keguruan dan Ilmu Pendidikan, Universitas Mahaputra Muhammad Yamin, 2021)
Homosexuality is also known as a disease or mental disorder. As a disease of course must be given treatment, so that the disease can be cured. However, based on Indonesian culture, it is considered that homosexuality is something that is deviant or something that is not normal. For this reason, in this study, we will discuss how these deviations form. The deviation in question is the dystonic ego in the novel Maroon (Luka the Writer) by Asrini Mahdia. In conducting this study, the researcher used a qualitative approach with a descriptive method with content analysis techniques. The results of this study are sexual deviations that occur in the main character (I) with a dystonic ego. However, after meeting a very kind and caring woman, my character begins to feel uncomfortable with her sexual orientation (homosexual ego dystonic), namely the homosexual attitude or behavior found in my character caused by past trauma, not getting love from parents, etc. Homosexuals that occur in the main character (I) tend to be ego dystonic homosexuals. Because before becoming a homosexual, my character was a normal man.